MENINGKATKAN MUTU ASPAL DI PERKERASAN JALAN YANG TELAH LAPUK DENGAN CARA DINGIN - Tjitjik Wasiah Suroso (Jurnal Jalan-Jembatan, 2009)
The quality of asphalt in road pavement is decreasing due to oxidation process and polymerization. Moreover, Indonesia is a tropical country where climatic factor can accelereate asphalt aging. There are two methods to improve the quality of asphalt, Firstly, by crack filling using asphalt or by emulsion asphalt with rejuvenated materials when road damage caused by hair cracks commanly called surface dressing. The second method is scrap materials from pavement added by additives or using fresh bitumen and aggregate commonly called recycling. The research showed that crack filling method increase asphalt quality in pavement and asphalt penetration from 10-11 to be 33-35 and ductility of asphalt from 14-15 cm to be 140cm, therefore pavement can arise two year service life. Cold recycling method increases the service life of pavement in moderate traffic up to 4 years. Keyword : Recycling, Additive materials, Aging, Asphalt mixture